Timing of reconstruction of the lower urinary tract in pediatric kidney transplant recipients: A CERTAIN multicenter analysis of current practice. (11th June 2022) - Patry, Christian; Höcker, Britta; Dello Strologo, Luca; Baumann, Lukas; Grenda, Ryszard; Peruzzi, Licia; Oh, Jun; Pape, Lars; Weber, Lutz T.; Weitz, Marcus; Awan, Atif; Carraro, Andrea; et al.
Abstract: Background: Preexistent LUTD are considered a hostile environment, which might negatively impact KTx survival. In such cases, surgical reconstruction of the bladder is required. However, there is still disagreement on the optimal timing of the reconstruction procedure. Methods: This is a multicenter analysis of data from the CERTAIN Registry. Included were 62 children aged 8.18 ± 4.90 years, with LUTD. Study endpoints were the duration of initial posttransplant hospitalization, febrile UTIs, and a composite failure endpoint comprising decline of eGFR, graft loss, or death up to 5 years posttransplant. Outcome was compared to matched controls without bladder dysfunction. Results: Forty‐one patients (66.1%) underwent pretransplant and 14 patients (22.6%) posttransplant reconstruction. Bladder augmentation was performed more frequently in the pretransplant (61%) than in the posttransplant group (21%, p  = .013). Outcome in the pre‐ and posttransplant groups and in the subgroups of patients on pretransplant PD with major bladder surgery either pre‐ ( n  = 14) or posttransplant ( n  = 7) was comparable. Outcomes of the main study cohort and the matched control cohort ( n  = 119) were comparable during the first 4 years posttransplant; at year 5, there were more events of transplant dysfunction in the study cohort with LUTD than in controls ( p  = .03). Conclusions: This multicenter analysis of the current practice of LUTD reconstruction in pediatric KTx recipients shows that pre‐ or posttransplant surgical reconstruction of the lower urinary tract is associated with a comparable 5‐year outcome.